2021
DOI: 10.1044/2021_jslhr-20-00227
|View full text |Cite
|
Sign up to set email alerts
|

Word Recognition and Word Prediction in Preschoolers With (a Suspicion of) a Developmental Language Disorder: Evidence From Eye Tracking

Abstract: Purpose This study compares online word recognition and prediction in preschoolers with (a suspicion of) a developmental language disorder (DLD) and typically developing (TD) controls. Furthermore, it investigates correlations between these measures and the link between online and off-line language scores in the DLD group. Method Using the visual world paradigm, Dutch children ages 3;6 (years;months) with (a suspicion of) DLD ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…It is possible that these weak relationships are specific to DLD and are related to the processing limitations that children with DLD experience. For example, children with DLD process sentences slower (Montgomery, 2006), are less able to retain information in phonological memory (Archibald & Gathercole, 2006), are slower to predict upcoming words in a sentence (van Alphen et al, 2021), and have difficulties sustaining attention to audio-linguistic stimuli (Ebert & Kohnert, 2011). These processing and attentional limitations may hamper using linguistic experiences for language learning resulting in weaker relations between home language environment measures and language skill.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these weak relationships are specific to DLD and are related to the processing limitations that children with DLD experience. For example, children with DLD process sentences slower (Montgomery, 2006), are less able to retain information in phonological memory (Archibald & Gathercole, 2006), are slower to predict upcoming words in a sentence (van Alphen et al, 2021), and have difficulties sustaining attention to audio-linguistic stimuli (Ebert & Kohnert, 2011). These processing and attentional limitations may hamper using linguistic experiences for language learning resulting in weaker relations between home language environment measures and language skill.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to a more reliable parental estimate of productive vocabulary. Another tentative explanation would be the use of prediction in production (van Alphen et al, 2021), which might also have impacted processing of our predictable rhyming stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies that address the phenomenon of language comprehension in children with DLD have been based on offline methodologies. Such offline measures provide useful information on the outcome of language processes; however, online technics allow capturing difficulties in the underlying language process (van Alphen et al, 2021). In this respect, Andreu et al (2013) suggested that the previous studies based on offline tools could have limitations when recording the real linguistic comprehension capacity of children with DLD.…”
mentioning
confidence: 99%